2001
DOI: 10.1021/bi0155899
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Functional Expression of a Human Intestinal Lactoferrin Receptor

Abstract: Lactoferrin (Lf), a major iron-binding protein in human milk, has been suggested to have multiple biological roles such as facilitating iron absorption, modulating the immune system, embryonic development, and cell proliferation. Our previous binding studies suggested the presence of a specific receptor for Lf (LfR) in the small intestine of newborn infants, which may facilitate iron absorption. We here report the cloning and the functional expression of the human intestinal LfR and the evidence of its involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
246
5
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(264 citation statements)
references
References 40 publications
(53 reference statements)
10
246
5
3
Order By: Relevance
“…Given that activation triggers the secretion of the basic lactoferrin [40] the tyrosylation reaction may have occurred in the medium. Binding to lactoferrin receptors may explain why the tyrosylated form also occurs in the soluble fraction [41]. In agreement with our findings it was recently shown that three lactoferrin isoforms of 75, 80, and 85 kDa were constitutively expressed in the plasma membrane and secondary granules of resting neutrophils [42].…”
Section: Discussionsupporting
confidence: 92%
“…Given that activation triggers the secretion of the basic lactoferrin [40] the tyrosylation reaction may have occurred in the medium. Binding to lactoferrin receptors may explain why the tyrosylated form also occurs in the soluble fraction [41]. In agreement with our findings it was recently shown that three lactoferrin isoforms of 75, 80, and 85 kDa were constitutively expressed in the plasma membrane and secondary granules of resting neutrophils [42].…”
Section: Discussionsupporting
confidence: 92%
“…Among the Stat6-dependent genes that were induced in lung and intestine during infection were IgA, calcium activated chloride channel 3, small proline rich proteins 2 and intelectin-2, which has recently been identified as a gene induced by nematode infection in the small intestine (Table 1) (Komiya, 1998;Pemberton, 2004b). Two intelectin genes have been described in mouse and man with high homology to a Xenopus oocyte granule lectin (Lee, 2001;Pemberton, 2004a;Suzuki, 2001b). Since human intelectin has been described to bind galactofuranose sugars present in cell walls of bacteria, fungi and protozoan parasites and therefore might play a role in immune defense, its mouse homolog was chosen here for further investigation (Daffe, 1990;Latge, 1994;Suzuki, 2001a;Suzuki, 2002;Tsuji, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Human intelectin-1 has independently been cloned as lactoferrin receptor from samples of human fetal intestine (Suzuki, 2001b). Lactoferrin is involved in antibacterial responses by either agglutinating bacteria or binding of iron, which lowers the available iron critically required for bacterial growth (Otto, 1992;Teraguchi, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Omentin has been identified in other tissues at lower expression levels and named intelectin (14), intestinal lactoferrin receptor (15), or endothelial lectin (16). It is expressed in intestinal Paneth cells (17), endothelial cells (16), and visceral adipose stromal-vascular cells (11).…”
mentioning
confidence: 99%